Complete genome sequence of Bacillus megaterium JX285 isolated from Camellia oleifera rhizosphere. (April 2019) - Huang, Fang-liang; Zhang, Yang; Zhang, Lin-ping; Wang, Shu; Feng, Ye; Rong, Nian-hang
Graphical abstract: Bacillus megaterium strain JX285, isolated from rhizosphere red soil sample, can solubilize inorganic phosphorus, which increases the amount of available phosphorus and promotes plant growth. We studied the genome of this strain and compared it with other bacteria. Highlights: The isolation of phosphate solubilized B. megaterium from the Camellia oleifera rhizosphere has not been previously reported. Release of the genome information of this strain will promote studies on the mechanisms of phosphate solubilization, which will improve the economic benefits of cultivation in red soil regions of China. Genes associated with organic acid production were observed in the JX285 genome, such as those encoding citrate synthase. Genes of the cblA cluster, which are regarded as toxic genes, were not detected using polymerase chain reaction, indicating that B. megaterium strain JX285 is not toxic to plants. Abstract: Bacillus megaterium strain JX285, isolated from rhizosphere red soil sample, can solubilize inorganic phosphorus, which increases the amount of available phosphorus and promotes plant growth. To investigate the mechanisms underlying phosphate solubilization, we sequenced the entire genome of B. megaterium strain JX285 (CGMCC 1.1621), which comprises a circular chromosome of 5, 066, 463 bp and seven plasmids of 167, 030, 128, 297, 60, 905, 134, 795, 9, 598, 37, 455, and 6332 bp, respectively. The whole genome sequence includes 5948 protein-coding genes, 124 tRNAs, and 29 rRNAs, and has been deposited at Genbank/EMBL/DDBJ with accession numbers CP018874–CP018881. We detected genes associated with organic acid production, which may be vital for phosphate conversion. Furthermore, phosphatase-encoding genes were also detected. The information embedded in the genome will assist in studying the mechanisms of phosphate solubilization. In conclusion, analysis of the JX285 genome will further our knowledge regarding this strain and may contribute to its biotechnological application.